Konservasi terumbu karang dengan bioreeftek di Perairan Kampung Bakaro Manokwari Papua Barat: Coral reefs conservation with bioreeftech in the Beach of Bakaro Village Manokwari West Papua - Mogea, Rina; Noya, Alce I.; Tururaja, Tresia S.; Lamadi, Rahmat; Tandililing, Jeanifer G.; Puspasari, Aninda; Maahury, Sevian A.; Bakri, Iskandar (IGKOJEI: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT  Bakaro Beach is one of the beach tourist destinations in Manokwari and is known as a fish calling place. Unfortunately this place was damaged due to fishing using bombs or tubas. The aim of this service activity is to provide an understanding of the importance of coral reef ecosystems and how to restore coral reefs using bioreeftek, ie technology that uses coconut shells as a medium for attaching coral planula larvae to form new individuals (coral). This is done to create new habitat or restore damaged coral. This technology is easy because it uses simple tools, using coconut shells as the main material and the process is not difficult, besides all the materials used are environmentally friendly. Coconut shells function as a place or container for coral planula larvae to settle after the larvae attach to the coconut shell substrate and are then transferred to damaged coral reefs. With the development of bioreeftek, it has become a new focus in preserving coral reef ecosystems.  Keywords: Coral Reef Restoration; Bioreeftek; Coconut Shells; Bakaro Beach; Environmental Conservation   ABSTRAK Pantai Bakaro tempat ini sebagai salah satu destinasi wisata pantai yang ada di Manokwari dan dikenal dengan tempat pemanggilan ikan.  Sayangnya tempat ini mengalami kerusakan akibat pengambilan ikan dengan menggunakan bom atau tuba. Tujuan kegiatan pengabdian ini yaitu memberi pemahaman mengenai pentingnya ekosistem terumbu karang dan cara melakukan pemulihan terumbu karang dengan bioreeftek yaitu teknologi yang memakai tempurung kelapa sebagai media menempelnya larva planula karang sampai membentuk individu baru (karang). Hal ini dilakukan untuk menciptakan habitat baru atau memulihkan kembali karang yang rusak.  Teknologi ini mudah sebab menggunakan alat sederhana yaitu tempurung kelapa sebagai bahan utama dan proses pengerjaannya tidak sulit, disamping itu juga semua bahan yang digunakan ramah lingkungan. Tempurung kelapa berfungsi untuk tempat atau wadah dari larva planula karang menetap setelah larvanya menempel pada subtrat tempurung kelapa maka dipindahkan ke terumbuh karang yang rusak. Dengan menggembangkan bioreeftek ini menjadi tumpuan baru dalam melestarikan ekosistem terumbu karang. Kata kunci: Pemulihan Terumbu Karang; Bioreeftek; Tempurung Kelapa; Pantai Bakaro; Pelestarian Lingkungan